Prevalence of Left Atrial Appendage Thrombus in Patients Anticoagulated With Direct Oral Anticoagulants: Systematic Review and Meta-analysis - Alqarawi, Wael (CJC Open, 2020)
BACKGROUND: Multiple studies have examined the prevalence of left atrial appendage thrombus (LAAT) in patients anticoagulated with direct oral anticoagulants (DOACs) and have reported conflicting results. METHODS: Studies reporting the prevalence of LAAT on transesophageal echocardiography (TEE) after 3 or more weeks of DOAC therapy were identified. The proportions of anticoagulated patients diagnosed with LAAT were pooled using random-effects models. Prespecified subgroup analyses by the indication of TEE (pre–atrial fibrillation [AF] ablation vs cardioversion) and TEE strategy (routine use vs selective) were conducted via stratification. RESULTS: Forty studies were identified: 22 full manuscripts and 18 abstracts. Only 11 studies performed TEE routinely. Most studies included patients with paroxysmal AF and low thromboembolic risk. The pooled prevalence of LAAT was 2.5% (95% confidence interval [1.6%-3.4%]). The prevalence of LAAT is lower in the pre-AF ablation group compared with pre-cardioversion (1.1% vs 4.0%, P = 0.033). Routine TEE strategy yielded a lower LAAT prevalence in both groups (0.1% vs 2.3%, P = 0.002 and 3.2% vs 5.8%, P = 0.432, respectively). CONCLUSION: The reported prevalence of LAAT on TEE in patients treated with DOACs is highly variable. Factors associated with a high LAAT prevalence were pre-cardioversion indication and selective TEE strategy. Routine use of TEE before AF ablation may not be warranted.